1990
DOI: 10.1111/j.1095-8649.1990.tb05938.x
|View full text |Cite
|
Sign up to set email alerts
|

Terrestrial locomotion in the climbing perch, Anabas testudineus (Bloch) (Anabantidea, Pisces)

Abstract: Climbing perches use the tail for forward propulsion when on land. The spiny gill covers are used to obtain purchase on the substratum. Unusually amongst teleosts, the opercular and subopercular bone are not bound strongly together into a single operculum. Instead they are joined only by a thin, flexible membrane, so that the fish has two sections of the gill cover hinged separately; the opercular on the suspensorium and the subopercular on the rearmost part of the lower jaw. The gill covers open very widely a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
33
0

Year Published

1997
1997
2016
2016

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(34 citation statements)
references
References 8 publications
1
33
0
Order By: Relevance
“…During drought, A. testudineus stays in pools associated with submerged woods and shrubs (Sokheng et al 1999) or buries under the mud (Rahman 1989). Furthermore, it can travel long distances on land between pools of water, covering several hundred meters per trip when the air is suYciently humid (Davenport and Abdul Martin 1990). Its air-breathing capacity and ability to survive on land have attracted a lot of attention in the past, but its ability to inhabit a brackish environment has been largely neglected until recently.…”
Section: Introductionmentioning
confidence: 98%
“…During drought, A. testudineus stays in pools associated with submerged woods and shrubs (Sokheng et al 1999) or buries under the mud (Rahman 1989). Furthermore, it can travel long distances on land between pools of water, covering several hundred meters per trip when the air is suYciently humid (Davenport and Abdul Martin 1990). Its air-breathing capacity and ability to survive on land have attracted a lot of attention in the past, but its ability to inhabit a brackish environment has been largely neglected until recently.…”
Section: Introductionmentioning
confidence: 98%
“…During drought, A. testudineus stays in pools associated with submerged woods and shrubs (Sokheng et al 1999) or buries under the mud (Rahman 1989). Furthermore, it can travel long distances on land between pools of water, covering several hundred meters per trip when the air is sufficiently humid (Davenport and Abdul Martin 1990). Its air-breathing capacity and ability to survive on land have attracted a lot of attention in the past, but its ability to inhabit a brackish environment has been neglected until recently.…”
mentioning
confidence: 98%
“…The ability to use oxygen directly from the atmosphere makes climbing perch less sensitive to low oxygen levels in water, and the low levels of DO during the experiments were not seen to affect the survival of the fish (Armbruster 1998). Many studies have shown that climbing perch can tolerate and adapt to extremely harsh environments such as low pH values, high temperatures, and especially low DO concentrations (Davenport and Abdulmatin 1990;Khoa and Huong 1993;Klepper et al 1992).…”
Section: Discussionmentioning
confidence: 96%